Pengaruh Fraksi Air Ekstrak Etanol Umbi Bawang Merah (Allium cepa L.) terhadap Kadar Kolesterol Total Serum Darah Tikus Putih - Erna Dwi Hastutik; Kisrini Kisrini; Dwi Ningsih (Jurnal Farmasi Indonesia, 2010)
Onion (Allium cepa L.) is one of medical plants that widely used, and onion tuber is supposed to have beneficial to decrease cholesterol level. The aim of this study was to find out the effect of water fraction of onion ethanol extract that given orally on decreasing total cholesterol level in blood serum of white rats wistar and to see the dose that gave the effect equal with simvastatin in decreasing total cholesterol level. The study to determine cholesterol level of the animal testing was conducted by CHOD-PAP method. Test animals were divided into 5 groups and each group consists of 5 rats. Group I as negative control was contain CMC 1%. Group II was contain CMC 1% and treated water fraction of onion etanol extracts with three variations of dose, namely 25, 50, 100 mg/200 g body wight obtained from the ethanol extract fraksinasi using water and ethyl acetate. Group III as positive control was contain simvastatin and CMC 1%. Test animals were given pig oil and cholesterol powder for one week until hypercholesterolemia condition, and then were given test preparation until the 14th day. The cholesterol level was measured on the 1st, 7st and 14st day. The results of this study were that water fraction of onion ethanol extracts that given orally could decrease total cholesterol level in blood serum of white male rat. According to the results of one way anova statistical test, it was indicated that water fraction of onion ethanol extracts of 100 mg/ 200 g body wight dose had the effect to decrease total cholesterol level equal with simvastatin.